Quantify the changes in landscape patterns and their impact on ecosystem services values using land use land cover data in the middle reaches of the Damodar river basin - Sougata; Chakrabortty, Druheen Chakrabortty (Acta Geographica Debrecina Landscape & Environment series, 2025)
Human activities continuously modify the landscape area for their purpose which forces the landscape structure to change continuously. Therefore, it is essential to examine the impact of changing landscape structure on Ecosystem services values (ESV). The study has quantified the dynamic of ESV using land use land cover data and landscape metrics. The study has applied the Costanza et al. (1997 &2014) method to estimate ESV in the Middle reaches of the Damodar River Basin area and the Getis-Ord Gi* technique to delineate the dynamic hot spot and cold spot region in ESV within the stipulated period. The study has shown that ESV varies with the changes in landscape structure. The diminishing of vegetation, agricultural land, water body area and the expansion of built-up area has shifted the ESV zone from the North-West part in 2000-2012 to the wider part of North-West and North-East in 2012-2023 and 2000-2023 periods and marked the North-West and North-East part as a more dynamic zone within the study period.